Comparison of two mathematical models for predicted human thermal responses to hot and humid environments. (April 2021) - Potter, Adam W.; Yermakova, Irena I.; Hunt, Andrew P.; Hancock, Jason W.; Oliveira, A. Virgilio M.; Looney, David P.; Montgomery, Leslie D.
Abstract: Purpose: We compared the accuracy and design of two thermoregulatory models, the US Army's empirically designed Heat Strain Decision Aid (HSDA) and the rationally based Health Risk Prediction (HRP) for predicting human thermal responses during exercise in hot and humid conditions and wearing chemical protective clothing. Methods: Accuracy of the HSDA and HRP model predictions of core body and skin temperature ( Tc, Ts ) were compared to each other and relative to measured outcomes from eight male volunteers (age 24 ± 6 years; height 178 ± 5 cm; body mass 76.6 ± 8.4 kg) during intermittent treadmill marching in an environmental chamber (air temperature 29.3 ± 0.1 °C; relative humidity 56 ± 1%; wind speed 0.4 ± 0.1 m∙s −1 ) wearing three separate chemical protective ensembles. Model accuracies and precisions were evaluated by the bias, mean absolute error (MAE), and root mean square error (RMSE) compared to observed data mean ± SD and the calculated limits of agreement (LoA). Results: Average predictions of Tc were comparable and acceptable for each method, HSDA (Bias 0.02 °C; MAE 0.18 °C; RMSE 0.21 °C) and HRP (Bias 0.10 °C; MAE 0.25 °C; RMSE 0.34 °C). The HRP averaged predictions for Ts were within an acceptable agreement to observed values (Bias 1.01 °C; MAE 1.01 °C; RMSE 1.11 °C). Conclusion: Both HSDA and HRP acceptably predict Tc and HRP acceptably predicts Ts when wearing chemical protective clothing during exercise in hot and humid conditions. Highlights: Compares component differences between the Heat Strain Decision Aid (HSDA) and the Health Risk Prediction (HRP) model. Compares the predictive accuracy of HSDA and HRP for predicting human thermal stress in hot and humid environments. Demonstrates the acceptable accuracy of the HSDA model for making predictions of core body temperature. Demonstrates the acceptable accuracy of the HRP model for making predictions of core body and skin temperature.